2018
DOI: 10.3233/cbm-170805
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of immune function, hemorheological alterations and prognosis in colorectal cancer patients with different traditional Chinese medicine syndromes

Abstract: Taken together, we conclude that patients with TCM deficiency syndrome has lower immune function and poorer prognosis while patients with TCM excess syndrome has higher immune function and better prognosis of CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In this study, the multivariate analysis confirmed TCM syndrome as an independent prognostic factor, and the KM analysis indicated that HBV-related HCC patients with TCM excess syndrome had the longest median survival time. Previous studies indicated that cancer patients with TCM deficiency syndrome have lower immune function and shorter survival time, while cancer patients with excess syndrome have better immune function and longer survival time, which supports the finding of our study [ 9 ]. Also, TCM can promote the antitumor effect by restoring immunosurveillance, including upregulating immunostimulatory factors and downregulating immunosuppressive factors [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the multivariate analysis confirmed TCM syndrome as an independent prognostic factor, and the KM analysis indicated that HBV-related HCC patients with TCM excess syndrome had the longest median survival time. Previous studies indicated that cancer patients with TCM deficiency syndrome have lower immune function and shorter survival time, while cancer patients with excess syndrome have better immune function and longer survival time, which supports the finding of our study [ 9 ]. Also, TCM can promote the antitumor effect by restoring immunosurveillance, including upregulating immunostimulatory factors and downregulating immunosuppressive factors [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…In TCM theory, TCM syndrome consists of a series of specific clinical symptoms, but there is no unified diagnostic standard of TCM syndromes currently. In our study, TCM syndromes of HBV-related HCC patients were determined on the basis of the “guidelines for diagnosis and treatment of primary liver cancer in China,” [ 8 ] the standard of excess and deficiency syndromes in “ Diagnostics of TCM ” (a textbook for universities and colleges of TCM in China), and a previous study [ 9 ]. In our study, TCM syndromes were classified into three types: excess syndrome, deficiency syndrome, and syndrome of intermingled deficiency and excess patterns.…”
Section: Methodsmentioning
confidence: 99%
“…The antitumor treatment of Traditional Chinese Medicine (TCM) has undergone thousands of years of clinical practice, and its efficacy is unquestionable. It is an important part of comprehensive treatment of malignant tumors [ 4 6 ]. Colorectal cancer (CRC) is the second most common malignant tumor in women and the third most common one in men which has high morbidity and mortality [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, surgical resection is still the only curative treatment for CRC patients. Nevertheless, due to its occult onset, most CRC patients are diagnosed in advanced stages when surgery is unavailable [4]. Another issue is that major complications occur on up to 15% patients, and postoperative recurrence and metastasis are quite common [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, due to its occult onset, most CRC patients are diagnosed in advanced stages when surgery is unavailable [4]. Another issue is that major complications occur on up to 15% patients, and postoperative recurrence and metastasis are quite common [4,5]. Neoadjuvant and adjuvant chemoradiotherapy is now generally accepted standard treatment for locally advanced CRC, with the aim of reducing recurrence and metastasis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%